The contract-relax proprioceptive neuromuscular facilitation (PNF) stretching can affect the dynamic balance in healthy men - Ghram,Amine (2016)
OBJECTIVE: This study aimed to investigate the effect of the contract-relax proprioceptive neuromuscular facilitation (CR PNF) stretching protocol on dynamic balance. METHODS: Twenty healthy young male performed two sessions in a randomized order; a session with CR PNF stretching protocol, and a session without the stretching protocol. Bipedal dynamic balance was measured in anterior-posterior and medio-lateral directions before and after the completion the two experimental sessions with eyes opened and closed. RESULTS: the present study showed that there is no significant difference between the two sessions (with vs without the CR PNF stretching protocol) in the anterior-posterior direction. However, in the medio-lateral direction, the CR PNF stretching protocol significantly enhanced dynamic balance, when compared with the no stretch protocol condition. CONCLUSION: This study concluded that CR PNF stretching might be effective to improve dynamic balance control.